(untitled) (Confluenţe Bibliologice, 2025)
The article focused on Training , English for Speciﬁc Purposes “, held in the Scientiﬁc Library USARB on the 4-5 April under the , Library Network Support Services: modernizing libraries in Armenia, Moldova and Belarus through reforming libraries and library staﬀ development [LNSS] , ﬁnancially supported by the Erasmus Programme + European Union, Capacity Building in the Field of Higher Education (CBNE). Trainers: Jerald Cavanagh BSc Econ, MSc, MA, Institute Librarian, Limerick Institute of Technology and Padraig Kirby BA (Hons) HdipLIS MSc (LIS), Senior Library Assistant, Limerick Institute of Technology International Institute of Technology Limerick, Republic of Ireland